(untitled) (Journal of Organizational Psychology, 2020)
This paper discussed modern macroeconomics vis-à-vis Islamic economics. A description is given of the relevant macroeconomic fields under relevant headings and then discussed, scrutinized and Islamic perspective offered. The paper believed that capitalist macroeconomy is unsustainable and detrimental to human welfare and environment and that Islamic model is the best model to sustain human welfare, environment and economic growth and the only option we have to replace capitalist system of economy.